Response of compacted bentonite to hyperalkalinity and thermal history - Rohini C. Kale (Nature Portfolio, 2021)
Abstract The use of compacted bentonite around the high-level nuclear waste canister (HLW) inside the deep geological repository (DGR) ensures the prevention of entry of active radionuclides in the atmosphere due to its noteworthy large swelling ability. In the eventual repository, the waste canister has a high (100 °C–200 °C) temperature initially, and it reduces over a vast period, which induces a thermal history over the compacted bentonite layer. The cement/concrete layer is constructed as a bulkhead or in the vaults or to support the access of galleries between a buffer and the host rock, and it degrades over the period. The hyperalkaline fluid is created when it percolates through the cement/concrete layer and comes in contact with the compacted bentonite. The contact of hyperalkaline fluid to compacted bentonite induced with thermal history can hamper the swell pressure characteristic of the bentonite. Therefore to determine the combined effect of hyperalkalinity to the thermal history induced compacted bentonite, swell pressure testing has been conducted on two compacted Barmer bentonites (B1 and B2) specimens with an initial dry density of 1.5 Mg/m3, 1.75 Mg/m3, and 2.0 Mg/m3 and saturated with distilled water as well as with hyperalkaline cement water (W/C = 1 und pH = 12.5) and heated to 110 °C and 200 °C. When the specimens were saturated with hyperalkaline cement water, the swell pressure exerted by both bentonites was noticeably reduced compared to specimens saturated with distilled water. Nevertheless, the time taken to full saturation was longer than distilled water for samples saturated with hyperalkaline cement water. Also, the decrease in swell pressure was observed in the samples subjected to thermal history than samples, which were tested without inducing thermal history in both the cases of hyperalkaline cement water and distilled water. The microstructural observations through XRD, FESEM and EDX revealed the clogging of pores due to the presence of non-swelling minerals.